Coloniality of biopolitics, eurocentric knowledges and decolonial genealogy - Sena, Guilherme Ribeiro dos Santos (Seven Editora, 2024)
The proposition of this article is the continuation of a series of researches carried out by the author in the last two years, both in the form of a research project and an article in the publication phase. To this end, the method of critical analysis is used the decolonial genealogy or genealogical decoloniality, a way of approximating the analysis erected by the French philosopher Michel Foucault of the forms of exercise of power and the decolonial critical theory to modernity/coloniality in the figure of the Peruvian sociologist Aníbal Quijano. In this way, it was possible to identify how Eurocentric knowledge is formed and acts together with the coloniality of knowledge (Eurocentrism) as mechanisms for maintaining epistemic and racist prejudice. In addition, a new way of understanding the complexity of the forms of subjection/subjection within the colonial context was proposed in the figure of the coloniality of biopolitics, a form of exercise of the coloniality of power and biopolitics at the micro, meso and macrophysical levels. DOI:https://doi.org/10.56238/sevened2024.018-001